Defective Granuloma Formation in Elderly Infected Patients - Daumas, Aurélie; Coiffard, Benjamin; Chartier, Céline; Ben amara, Amira; Alingrin, Julie; Villani, Patrick; Mege, Jean-Louis (Frontiers in Cellular and Infection Microbiology, 2020)
Granulomas are compact structures formed in tissues by the immune system in response to aggressions. The in vitro formation of granulomas using circulating mononuclear cells is an innovative method to easily assess the immune response of patients. Monitoring the efficiency of mononuclear cells from patients to form granulomas in vitro would help improve their therapeutic management. Circulating mononuclear cells from 23 elderly patients with sepsis and 24 elderly controls patients were incubated with Sepharose beads coated with either BCG or Coxiella burnetii extracts. The formation of granulomas was measured over 9 days. Most healthy elderly patients (92%) were able to form granulomas in response to BCG and Coxiella burnetii extracts compared to only 48% of infected elderly patients. Undernutrition was significantly associated with impaired granuloma formation in healthy and infected patients. Granulomas typically comprise epithelioid cells and multinucleated giant cells, however, these cells were not detected in samples obtained from patients unable to form granulomas. We also found that the impairment of granuloma formation was associated with reduced production of tumor necrosis factor without overproduction of interleukin-10. Finally, all genes specifically modulated in granulomatous cells were down-modulated in patients with defective granuloma formation. TNFSF10 was the only M1 gene markedly upregulated in patients who did not form granulomas. Our study suggest that defective granuloma formation may be a measurement of altered activation of immune cells which can predispose to nosocomial infections in elderly patients.